A NIR-Activated and Mild-Temperature-Sensitive Nanoplatform with an HSP90 Inhibitor for Combinatory Chemotherapy and Mild Photothermal Therapy in Cancel Cells - Yingying Peng; Hanlin Jiang; Bifei Li; Yue Liu; Bing Guo; Wei Gan (MDPI AG, 2023)
Mild photothermal therapy (PTT) shows great potential to treat cancers while avoiding unwanted damage to surrounding normal cells. However, the efficacy of mild PTT is normally moderate because of the low hyperthermia temperature and limited light penetration depth. Chemotherapy has unlimited penetration but often suffers from unsatisfactory efficacy in view of the occurrence of drug resistance, suboptimal drug delivery and release profile. As a result, the combinatory of chemotherapy and mild PTT would integrate their advantages and overcome the shortcomings. Herein, we synthesized an NIR-activatable and mild-temperature-sensitive nanoplatform (BDPII-gel@TSL) composed of temperature-sensitive liposomes (TSL), heat shock protein 90 (HSP90) inhibitor (geldanamycin) and photothermal agent (BDPII), for dual chemotherapy and mild PTT in cancer cells. BDPII, constructed with donor-acceptor moieties, acts as an excellent near-infrared (NIR) photothermal agent (PTA) with a high photothermal conversion efficiency (80.75%). BDPII-containing TSLs efficiently produce a mild hyperthermia effect (42 °C) under laser irradiation (808 nm, 0.5 W cm−2). Importantly, the phase transformation of TSL leads to burst release of geldanamycin from BDPII-gel@TSL, and this contributes to down-regulation of the overexpression of HSP90, ensuring efficient inhibition of cancer cell growth. This research provides a dual-sensitive synergistic therapeutic strategy for cancer cell treatment.